No Payoff from Time Off? Mandated Paid Vacation and Late-Career Employment - Simon Bensnes; Øystein Hernaes; Max-Emil M. King (Institute of Labor Economics (IZA), 2025)
This study examines the impact of receiving one additional week of paid vacation on labor market attachment among Norwegian workers aged 60+. Employing a triple-differences estimation strategy, we exploit age-based eligibility thresholds before and after a 2009 reform to identify causal effects. Our findings indicate that the extra leave has negligible effects on both employment, sickness absence and disability benefit receipt in the year workers first receive it. If anything, some workers use the additional vacation time to increase earnings from secondary employers. The results imply that policymakers should consider alternative measures to mandated leave to support an aging workforce.
Keywords: H8; I12; J22; J26; 330; paid vacation; older workers; labor supply; triple-differences; public policy